Language and motor function thresholds during pediatric extra-operative electrical cortical stimulation brain mapping. Issue 10 (October 2017) - Zea Vera, Alonso; Aungaroon, Gewalin; Horn, Paul S.; Byars, Anna W.; Greiner, Hansel M.; Tenney, Jeffrey R.; Arthur, Todd M.; Crone, Nathan E.; Holland, Katherine D.; Mangano, Francesco T.; Arya, Ravindra
Highlights: Electrical stimulation mapping functional and after-discharge thresholds are directly related. Language and motor thresholds exceed after-discharge thresholds depending on the age. This raises concerns about safety and neurophysiologic validity of electrical stimulation mapping. Abstract: Objective: To examine current thresholds and their determinants for language and motor mapping with extra-operative electrical cortical stimulation (ECS). Methods: ECS electrocorticograph recordings were reviewed to determine functional thresholds. Predictors of functional thresholds were found with multivariable analyses. Results: In 122 patients (age 11.9 ± 5.4 years), average minimum, frontal, and temporal language thresholds were 7.4 (± 3.0), 7.8 (± 3.0), and 7.4 (± 3.1) mA respectively. Average minimum, face, upper and lower extremity motor thresholds were 5.4 (± 2.8), 6.1 (± 2.8), 4.9 (± 2.3), and 5.3 (± 3.3) mA respectively. Functional and after-discharge (AD)/seizure thresholds were significantly related. Minimum, frontal, and temporal language thresholds were higher than AD thresholds at all ages. Minimum motor threshold was higher than minimum AD threshold up to 8.0 years of age, face motor threshold was higher than frontal AD threshold up to 11.8 years age, and lower subsequently. UE motor thresholds remained below frontal AD thresholds throughout the age range. Conclusions: Functional thresholds are frequently above AD thresholds in younger children. Significance: These findings raise concerns about safety and neurophysiologic validity of ECS mapping. Functional and AD/seizure thresholds relationships suggest individual differences in cortical excitability which cannot be explained by clinical variables.